2019
DOI: 10.1371/journal.pone.0225749
|View full text |Cite
|
Sign up to set email alerts
|

An add-on training program involving breathing exercises, cold exposure, and meditation attenuates inflammation and disease activity in axial spondyloarthritis – A proof of concept trial

Abstract: ObjectivesThe primary objective of this trial was to assess safety and anti-inflammatory effects of an add-on training program involving breathing exercises, cold exposure, and meditation in patients with axial spondyloarthritisMethodsThis study was an open-label, randomised, one-way crossover clinical proof-of-concept trial. Twenty-four patients with moderately active axial spondyloarthritis(ASDAS >2.1) and hs-CRP ≥5mg/L were included and randomised to an intervention (n = 13) and control group (n = 11) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 13 publications
0
47
0
1
Order By: Relevance
“…The WHM is based on cold exposure and special meditation techniques and was developed by a Dutch athlete named Wim Hof who exposed himself to extreme cold temperatures. The WHM consists of three main components: 1) breathing exercises, 2) various types of cold exposure, 1 , 2 and meditation related to mindful body awareness, including enhancement of willpower and self-awareness. 3 6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The WHM is based on cold exposure and special meditation techniques and was developed by a Dutch athlete named Wim Hof who exposed himself to extreme cold temperatures. The WHM consists of three main components: 1) breathing exercises, 2) various types of cold exposure, 1 , 2 and meditation related to mindful body awareness, including enhancement of willpower and self-awareness. 3 6 …”
Section: Introductionmentioning
confidence: 99%
“…The WHM is based on cold exposure and special meditation techniques and was developed by a Dutch athlete named Wim Hof who exposed himself to extreme cold temperatures. The WHM consists of three main components: 1) breathing exercises, 2) various types of cold exposure, 1,2 and meditation related to mindful body awareness, including enhancement of willpower and self-awareness. [3][4][5][6] There are only a few studies on this novel training program and its psychophysiological effects, but findings suggest that the WMH has positive effects on immune and endocrine functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breathing techniques and meditation have shown to decrease inflammation in Axial Spondyloarthritis (Buijze et al, 2019). Breathing techniques, especially the expiratory techniques improve lung functions, and immune response in bronchial asthma patients (Asimakos et al, 2018).…”
Section: Yogic Breathing On Stress Levels and Immunitymentioning
confidence: 99%
“…Moreover, the authors showed a correlation between the decrease in circulating calprotectin following the program and improved symptoms. In another study, published in 2019 by Buijze et al, a slight decrease in calprotectin concentration was observed following their program but was not significant in patients with spondyloarthritis [ 86 ]. This result may be explained by the program’s content, which consisted of breathing exercise, cold exposure, and meditation without any muscular mobilization exercise, unlike Levitova et al [ 85 ].…”
Section: Effect Of Exercise Intensity On Calprotectin Levelmentioning
confidence: 99%